IMPLEMENTASI NILAI-NILAI EKSISTENSIALISME DALAM PRAKTIK PENDIDIKAN MODREN - Nurfalah Daulay, Fadil; Jalaluddin, Husnan; Puspika Sari , Herlini (Jurnal Pendidikan Agama Islam, 2024)
The philosophy of existentialism, is a philosophy with the main thought being "existence precedes the essence" that man exists first, then in life he gives meaning or essence to his life by focusing on individual experiences. Existentialism gives individuals a way of thinking about life, what it means to me, what is true for me. Existentialist epistemology assumes that individuals are responsible for their own knowledge. The main source of knowledge is personal experience. An idealist teacher according to existentialists is a teacher who provides an open dialogue space for students to find their meaning. Students get broad opportunities to learn something that interests them, so they can find their identity. Appropriate learning methods according to existentialists are dialogue, role playing, and other methods that give freedom for students to explore meaning in themselves. Because the main task of education is to stimulate every human being to be aware of the responsibility to create meaning and definition of himself.